Foetal Movement Information and Maternal Concerns in the Third-Trimester: Findings of an Aotearoa New Zealand National Survey - Bradford, Billie F; Thompson, John MD; McKinlay, Christopher JD; Dukkipati, Likhit S; Cronin, George D; Waller, Nimisha; McAra-Couper, Judith; Cornwall, Tania; McCowan, Lesley ME; Cronin, Robin S (Wiley, 2026)
BACKGROUND: Promoting awareness of foetal movement (FM) is a recognised approach to addressing preventable stillbirth. However, provision of information is inconsistent, and rates of presentation for decreased FM may vary by maternal factors. Information is lacking on maternal views of FM information and knowledge of actions if concerned about FM. AIMS: To describe women's views of FM during late pregnancy in Aotearoa-New Zealand (Aotearoa-New Zealand), including factors that influence maternal actions if concerned. MATERIALS AND METHODS: Online survey of women with singleton third-trimester pregnancies in Aotearoa-New Zealand. Multivariable analysis adjusted for maternal factors. RESULTS: Eligible participants comprised European (1042, 63.5%), Māori (266, 16.2%), Pacific (119, 7.3%), Asian (160, 9.8%) and Other (35, 2.1%). Over half were nulliparous (916, 55.9%) and early third-trimester (median 31, IQR 28-34). Most (1366, 83.3%) had been concerned about FM. Groups that were less likely to seek advice when concerned, included Māori (aOR 0.69, 95% CI 0.51%-0.93%, p = 0.02), Pacific (aOR 0.58, 95% CI 0.38%-0.88%, p = 0.01) and parous (aOR 0.73, 95% CI 0.59%-0.90%, p = 0.003) women. Advice seeking was also less likely with a doctor as the main maternity provider (aOR 0.59, 5% CI 0.39%-0.92%, p = 0.02) compared to a midwife, and those who received fewer than recommended antenatal visits (aOR 0.55, 95% CI 0.34%-0.88%, p = 0.01). CONCLUSIONS: This study identified that FM worries are common in the third-trimester in Aotearoa-New Zealand. Yet, some groups of women were less likely to seek advice when concerned, indicating opportunities to reduce inequity and address barriers to accessing care.
Keywords: antenatal care; foetal activity; foetal movement; pregnancy; pregnant women; 3215 Reproductive Medicine; 4204 Midwifery; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Women's Health; Pregnancy; Maternal Health; Reproductive health and childbirth; 3 Good Health and Well Being; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services; Obstetrics & Reproductive Medicine; 3215 Reproductive medicine; 4204 Midwifery; Humans; Female; Pregnancy; New Zealand; Pregnancy Trimester, Third; Adult; Fetal Movement; Health Knowledge, Attitudes, Practice; Prenatal Care; Young Adult; Surveys and Questionnaires; Humans; Female; Pregnancy; New Zealand; Pregnancy Trimester, Third; Adult; Fetal Movement; Health Knowledge, Attitudes, Practice; Prenatal Care; Young Adult; Surveys and Questionnaires